2020
DOI: 10.21203/rs.3.rs-113896/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sight of parasitoid wasps accelerates sexual behavior and upregulates a micropeptide gene in Drosophila

Abstract: Parasitoid wasps inflict widespread death upon the insect world. Hundreds of thousands of parasitoid wasp species kill a vast range of insect species, and many such wasps are used globally to control insect pests. Insects have evolved defensive responses to the threat of wasps, some cellular and some behavioral. However, the nature of these responses and the mechanisms that underlie them await further exploration. Here we find an unexpected response of adult Drosophila to the presence of certain parasitoid was… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…There is building evidence that immune-induced AMPs and AMP-like genes affect the nervous system. Loss of Metchnikowin protects flies from neurodegeneration after traumatic brain injury (Swanson et al 2020), Induced by infection (IBIN) regulates behavioural changes in flies after seeing parasitoid wasps (Ebrahim et al 2021), epidermal nematode AMPs trigger motor neuron autophagy (Lezi et al 2018) and sleep (Sinner et al 2021) after infection, and loss of Diptericin B produced by the fat body leads to memory deficits in Drosophila (Barajas-azpeleta et al 2018). This last example is intriguing, as Diptericin B also encodes a polypeptide maturated by furin cleavage, and its effect on memory was derived from peptide secreted into the hemolymph by the fat body and not from neural expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is building evidence that immune-induced AMPs and AMP-like genes affect the nervous system. Loss of Metchnikowin protects flies from neurodegeneration after traumatic brain injury (Swanson et al 2020), Induced by infection (IBIN) regulates behavioural changes in flies after seeing parasitoid wasps (Ebrahim et al 2021), epidermal nematode AMPs trigger motor neuron autophagy (Lezi et al 2018) and sleep (Sinner et al 2021) after infection, and loss of Diptericin B produced by the fat body leads to memory deficits in Drosophila (Barajas-azpeleta et al 2018). This last example is intriguing, as Diptericin B also encodes a polypeptide maturated by furin cleavage, and its effect on memory was derived from peptide secreted into the hemolymph by the fat body and not from neural expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in nematodes have also shown that an immune-induced polypeptide (NLP-29) binds to a G-protein coupled receptor (NPR-12) triggering neurodegeneration through activation of the NPR-12-dependent autophagy pathway (Lezi et al 2018), and injury triggers epidermal AMPs including NLP-29 to promote sleep (Sinner et al 2021). Drosophila AMPs have also recently been shown to regulate behaviours after seeing parasitoid wasps (Ebrahim et al 2021), during feeding with different bacteria (Kobler et al 2020), or following infection (Hanson et al 2021). In humans, the Cathelicidin gene encodes the AMP LL-37, which is implicated in glia-mediated neuroinflammation and Alzheimer's disease (Lee et al 2015;De Lorenzi et al 2017), alongside evidence of Alzheimer's being an infectious syndrome (Dominy et al 2019); though the importance of this process is debated (Abbott 2020).…”
Section: Introductionmentioning
confidence: 99%
“…No pathogenic allelic variants of genes known to cause monogenic CPP (KISS1 receptor, KiSS-1 metastasis suppressor, makorin ring finger protein 3 and δ like non-canonical Notch ligand 1) (26-28) were found in the present case. Perhaps hints can be taken from other biological studies; for example, adult Drosophila accelerate their mating behavior to defend against the threat of certain parasitic wasps (29). It is unclear whether CPP occurring in BBS-10 would be a prelude of gonad dysplasia (30) or a self-protection mechanism of human reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a large number of long ncRNAs (lncRNAs; >200 nt) show differential expression in these mutants (Figure 6C-D). Amongst the lncRNAs upregulated in both tuSz 1 and hop Tum , Induced by infection (IBIN) is the only lncRNA that has been studied in the context of Drosophila immunity, although it has been proposed that IBIN encodes a short peptide that confers its function (Valanne et al 2019;Ebrahim et al 2021). The significant upregulation of lncRNAs in both genotypes highlights the potential importance of lncRNAs in mediating immune priming and autoimmune responses.…”
Section: Rel/nfκb Transcriptional Activity Is Associated With Pro-inflammatory Signaling Inmentioning
confidence: 99%